2014
DOI: 10.2337/dc13-1861
|View full text |Cite
|
Sign up to set email alerts
|

Potential Overtreatment and Undertreatment of Diabetes in Different Patient Age Groups in Primary Care After the Introduction of Performance Measures

Abstract: OBJECTIVE To assess whether after the introduction of diabetes performance measures decreases in undertreatment correspond with increases in overtreatment for blood pressure (BP) and glycemic control in different patient age groups. RESEARCH DESIGN AND METHODS We conducted a cohort study using data from the Groningen Initiative to Analyse Type 2 Diabetes Treatment (GIANTT) database. General practices were included when data w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…Out of 7698 combined search results, 53 articles were identified that reported at least 1 measure of therapeutic inertia in the management of hyperglycaemia in individuals with type 2 diabetes . The main reasons for exclusion of publications other than duplicates and those covering irrelevant topics were that they reported non‐original research (eg, editorials, letters, comments and guidelines) or they were congress abstracts (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Out of 7698 combined search results, 53 articles were identified that reported at least 1 measure of therapeutic inertia in the management of hyperglycaemia in individuals with type 2 diabetes . The main reasons for exclusion of publications other than duplicates and those covering irrelevant topics were that they reported non‐original research (eg, editorials, letters, comments and guidelines) or they were congress abstracts (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Articles mainly reported data from cohort studies, using data from medical records or chart reviews, or from claims, clinical research or administrative databases. Four articles reported results from cross‐sectional studies, and the data were collected using provider questionnaires or surveys . A single publication reported results from a randomized clinical trial that evaluated the impact of physician education on the management of individuals with type 2 diabetes, and another provided results from a post hoc analysis of a randomized controlled trial …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations